Annona muricata reduced proliferation caused by Cycas revoluta in wistar rats. - MICHODJEHOUN, Loetitia; Hoteyi, Ismael; KOUKOUI, RAHAMANE; AIVODJI, Natacha; Assou, Eudoxie K.; SEZAN, ALPHONSE (My University, 2018)
The purpose of this work is to determine the phytochemic composition of the ethyl extracts of the sheets of Annona muricata, in order to check of them the antineoplasm effects (anti-cancer) on cancer of the liver to the Benin.For this fact, an ethyl extraction using powder of sheets dried of Annona muricata and ethanol 90° was initially carried out. The screening phytochimic of the sheets of the plant was carried out by the method of Hougton and Raman. And ????nally the antineoplasm activity (anti-cancer) was evaluated by dosage of the parameters ALAT, ASAT and proteins total on grundings livers of Wistars rats, at the cancer of the liver was armature as a preliminary by exposure to the powder of Cycas revoluta through a diet composed to 5% of this powder and a drink water containing an amount de10mg/kg powder of Cycas revoluta. The results of the screening revealed the presence of several chemical compounds equipped with various properties to varied concentrations. The identi????ed chemical compounds are: reducing compounds, leuco-anthocyanes, tanins, ????avonoïdes, coumarins, mucilages and triterpenes. The antineoplasm activity (anti-cancer) was effective by administration of an amount of 100 mg/kg of ethyl extracts of the sheets of Annona muricata. This activity showed a variation of intensity according to the mode and the duration of administration of the extracts
Keywords: Annona muricata; Cycas revoluta; cancer of the liver; antineoplasm; extracted; Benin